Inter-monitor reliability and validity of the fibion accelerometers in a laboratory-based study of functional activities - Ashokan Arumugam; Zaineb Ghannami; Mahnaz Mahallati; Hala Al-Shams; Shaza Ahmed; Hager Khaled; Maha Hussein; Hanan Youssef Alkalih; Alexander H.K. Montoye; Kimberly Clevenger; Arto J. Pesola (PLoS ONE, 2025)
Background Accelerometer-based physical activity monitors are designed for placement on several body locations, with popular sites being the wrist, waist/hip, and thigh. Thigh placement is particularly valued for its accuracy in measuring postures and related energy expenditures. However, exploring the outcomes of different thigh wear locations remains an area for further research. This study investigated the inter-monitor reliability of Fibion accelerometers for energy expenditure and activity type classification, and their validity by comparing the Fibion’s activity classification against direct observation of a structured activity protocol as the reference standard. Methods Thirty healthy, young adults (aged 21.83 ± 2.80 years; 15 women) wore six Fibion accelerometers on three locations (proximal thigh, 10 cm above the patella, and the front trouser pocket) on both thighs while performing 11 functional activities for 70 minutes in a laboratory setting. Inter-monitor reliability for measuring energy expenditure, activity type and intensity, and accuracy for activity type and intensity classification of the pre-defined functional activities were assessed. Validity was assessed for classifying activity type and intensity. Results Reliability estimates (intraclass correlation coefficients (ICC 3, k)) implied good to excellent inter-monitor reliability for measuring energy expenditure during nearly all activities. Furthermore, energy expenditure measurements were equivalent between accelerometers in both trouser pockets, and proximal and distal thighs within a bound of ±.1.60 kcal/min. However, the right pocket was not equivalent to either the right proximal thigh or the right distal thigh. The mean activity classification accuracy ranged from 87–92% for activity type and 91–94% for activity intensity for the chosen activities, irrespective of the accelerometer location or side of the body (right vs. left). Conclusion The Fibion accelerometers reliably measure energy expenditure and accurately classify activity type/intensity for nearly all functional activities, regardless of the thigh wear location or side of the body. However, interchanging pocket and thigh placements is not recommended. Similar studies in free-living settings are further warranted.